Chapter 5 Fixed-line broadband From ADSL to FTTH - Ida, Takanori (Taylor & Francis, 2019)
Japan's high-speed Internet access services such as ADSL, CATV Internet and FTTH are considered the cheapest and fastest state-of-the-art services drawing international attention. In this book the author introduces the current status of broadband services in Japan and their recent development in competition policy. An econometric model is proposed and discussed to analyse access demand. The purpose of the analysis is to understand quantitively the current status of the rapidly developing Japanese broadband services while providing an academic and practical basis for conceiving prospective competition policies.